2015
DOI: 10.12669/pjms.312.6762
|View full text |Cite
|
Sign up to set email alerts
|

Association of geographical distribution of air quality index and type 2 diabetes mellitus in Isfahan, Iran

Abstract: Objectives:Air pollution is a hazardous environmental problem with several adverse health effects including its impact on the development of chronic diseases as diabetes mellitus. This study aimed to investigate the association of geographical distribution of air quality index (AQI) and type 2 diabetes mellitus in an air-polluted city by using geographic information system (GIS).Methods:This cross-sectional study was conducted in Isfahan, Iran. The records that have been registered from 2009 to 2012 in major r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Two ecological studies also suggest higher PM 2.5 levels to be associated with higher T2DM rates [ 78 , 125 ]. Several studies nonetheless found no significant or strong association for NO x [ 87 ], NO 2 [ 86 , 87 , 118 ], PM 10 [ 87 , 126 ], PM 2.5 [ 87 , 114 ], lower air quality [ 127 ], SO 2 (sulphur dioxide) [ 128 ], and benzo alpha pyrene [ 114 ]. One study demonstrated back extrapolated pollutant levels of NO 2 and NO x to be significantly associated with increased T2DM risk [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two ecological studies also suggest higher PM 2.5 levels to be associated with higher T2DM rates [ 78 , 125 ]. Several studies nonetheless found no significant or strong association for NO x [ 87 ], NO 2 [ 86 , 87 , 118 ], PM 10 [ 87 , 126 ], PM 2.5 [ 87 , 114 ], lower air quality [ 127 ], SO 2 (sulphur dioxide) [ 128 ], and benzo alpha pyrene [ 114 ]. One study demonstrated back extrapolated pollutant levels of NO 2 and NO x to be significantly associated with increased T2DM risk [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study in Iran on the association of geographical distribution of air quality index and incidence rate of T2D using a geographic information system[ 38 ] showed that the number of participants with diabetes was higher in highly polluted areas compared to areas with the lower levels of air pollution, however, there was no significant correlation between the distribution of patients with diabetes and air pollution level. It is worth noting that the influence of air pollutants on the incidence rate of diabetes mellitus or blood parameters was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the influence of air pollutants on the incidence rate of diabetes mellitus or blood parameters was not assessed. [ 38 ] Another study in Iran[ 15 ] investigated the association of T2D prevalence with exposure to high levels of PM10 in adults between 2006 and 2011 in five large cities (Tehran, Ahwaz, Shiraz, Kermanshah, and Isfahan),[ 15 ] grouping the cities to Group 1 (Tehran, Shiraz with PM10 concentration <100 μg/m 3 ), and Group 2 (Kermanshah, Ahwaz, Esfahan, with PM10 concentration >100 μg/m 3 ). The 5-year average of PM10 concentration was higher in Group 2 compared to group 1.…”
Section: Discussionmentioning
confidence: 99%
“…PM 2.5 1 , 14 and AQI 27 can vary depending on seasons, time of the day and locations in the same city 26 . Various studies from India 11 , 14 , 28 , 29 and other parts of the world 30 - 32 have explored geographic information system (GIS)-based tools, e.g ., inverse distance weighting (IDW), kriging, etc ., to estimate the spatio-temporal distribution of air pollutants and its associated heath impact. GIS is a powerful technique that can be used to accurately analyze the spatial and temporal patterns of respiratory morbidity 32 , chemistry of pollutants and localization of the area of potential threat 33 .…”
mentioning
confidence: 99%